Strategy Planning Practices and Performance: A Case Study in Road Transport Department - Hafsah, Abdul Aziz (2011)
This study is conducted to present findings on strategic planning practices, issues and influences of strategic planning in relation to performances of the Road Transport Department in Putrajaya, and Wilayah Persekutuan Kuala Lumpur. The research design used a qualitative method and case study research approach. A total of 10 respondents were interviewed in this study. Data was collected through face to face interviews, which used open ended questions. Data is analyzed based on the data gathered from the semi-structured interviews. The results show that the practices of strategic planning in the Road Transport Department included the element of environmental scanning and strategy formulation during the process of strategy planning. Thus, strategic planning practices are relevant based on the model selected. Apart from that, issues of strategic planning were also raised by the respondents and they suggested several solutions to overcome these problems in order to produce the desired result. Overall, strategic planning in the Road Transport Department has increased organizational performance.